First record of the West Nile virus bridge vector Culex modestus Ficalbi (Diptera: Culicidae) in Belgium, validated by DNA barcoding - de Wolf, Katrien; Vanderheyden, Ann; Deblauwe, Isra; Smitz, Nathalie; Gombeer, Sophie; Vanslembrouck, Adwine; Meganck, Kenny; Dekoninck, Wouter; de Meyer, Marc; Backeljau, Thierry; Müller, Ruth; van Bortel, Wim (Zootaxa, 2021)
A thorough knowledge of the presence and spatio-temporal distribution patterns of vector species are pivotal to assess the risk of mosquito-borne diseases in Europe. In 2018, a Culex larva was collected during routine monitoring activities to intercept exotic Aedes mosquito species in the port of Antwerp (Kallo, Belgium). The larva, collected from a pond in mid-September, was morphologically identified as Culex modestus, and this identification was subsequently confirmed by COI barcoding. It is the first confirmed record of this West Nile virus bridge vector in Belgium. The present study also demonstrates the value of DNA-based identification techniques to validate the presence of potential vector species.